Efeito do bioestimulante em sistema silvipastoril e monocultivo sobre a emissão de óxido nitroso - Bernardes, Carolina Volpini [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The world population growth has promoted an increase in the demand for food of animal origin. In addition to the challenges in increasing production, the agricultural sector also faces another challenge: the intensification of greenhouse gas emissions (CO2, N2O, O3, NH4). Strategies such as the use of biostimulants and silvopastoral systems have been tested for N2O mitigation. This study aimed to evaluate the use of biostimulants in different forage production systems (full sun and silvopastoral) regarding nitrous oxide emission. The experiment was carried out from January to May 2020, arranged in a completely randomized design with 5 replications, in a 2 x 2 factorial scheme. The treatments were the two systems: silvopastoral and full sun; and application of Biotrac®: with and without. Statistical analyzes were performed using the SISVAR program. The effects of treatments and their interactions were evaluated using the F test in analysis of variance (ANOVA). Multiple comparisons of treatment means, if significant, were tested using the Tukey test at 10% probability. Daily flows had greater variation in emission during the 1st cycle. In the 2nd, 3rd and 4th cycles there was a drop in emissions. In the full sun system, the application of the biostimulant did not generate a difference in N2O emission, whereas in the silvopastoral system, the 28application of the biostimulant resulted in lower N2O emission, showing an interaction between integrated systems and the use of biostimulant. Needing further studies of this interaction, such as the dose to be applied.

O crescimento populacional mundial tem promovido aumento da demanda por alimentos de origem animal. Além dos desafios no aumento da produção, o setor agropecuário enfrenta também outro desafio: a intensificação das emissões dos gases de efeito estufa (CO2, N2O, O3, NH4). Estratégias como a utilização de bioestimulantes e sistemas silvipastoris vem sendo testadas para a mitigação de N2O. Objetivou-se avaliar o uso de bioestimulante em diferentes sistemas de produção de forragem (pleno sol e silvipastoril) quanto à emissão de óxido nitroso. O experimento foi realizado de janeiro a maio de 2020, disposto em delineamento inteiramente casualizado com 5 repetições, em esquema fatorial 2 x 2. Os tratamentos foram os dois sistemas: silvipastoril e pleno sol; e aplicação de Biotrac®: com e sem. As análises estatísticas foram realizadas pelo programa SISVAR. Os efeitos dos tratamentos e suas interações foram avaliados usando o teste F em análise de variância (ANOVA). Comparações múltiplas das médias dos tratamentos, se significativas, foram testadas usando o teste Tukey a 10% de probabilidade. Os fluxos diários tiveram maior variação na emissão durante o 1º ciclo. Nos 2º, 3º e 4º ciclos houve queda nas emissões. No sistema pleno sol, a aplicação do bioestimulante não gerou diferença na emissão de N2O, já no sistema silvipastoril, a aplicação do bioestimulante resultou na menor emissão de N2O, mostrando uma interação entre sistemas integrados e o uso de bioestimulante. Necessitando de maiores estudos dessa interação, como a dose a ser aplicada.
Effect of biostimulant in silvopastoral and monoculture systems on nitrous oxide emission
Keywords: Ascophyllum; Capineira; Gases estufa